A comparison of outcomes and survival between Victoria and Denmark in lung cancer surgery: opportunities for international benchmarking. Issue 5 (22nd October 2021) - Stenger, Michael; Jakobsen, Erik; Wright, Gavin; Zalcberg, John; Stirling, Robert G.
Abstract: Backgrounds: Victoria (Australia) and Denmark have comparable population sizes and high‐quality healthcare systems. Lung cancer surgery, however, is performed in more than 20 Victorian hospitals compared to four in Denmark. Such differences in centralization may influence outcomes. We engaged clinical quality registries to enable international benchmarking by exploring patterns of lung cancer surgery including mortality and survival. Methods: All patients undergoing lung cancer surgery between 2015 and 2018 registered in the Victorian Lung Cancer Registry and the Danish Lung Cancer Registry were included. Analyses on stage concordance, 30 and 90‐day mortality, and overall survival were restricted to a selected subgroup with NSCLC and no neo‐adjuvant therapy or metastatic disease and only one operation. Results: We included 1554 Victorian and 4319 Danish patients. The resection rate was 26.3% in Victoria and 28% in Denmark, but a higher proportion of Victorian patients underwent wedge resection (19.1% versus 8.8%). Stage concordance was 59.6% and 54.9% in Victoria and Denmark, respectively. The 30‐ and 90‐day mortality was 1.3% and 2.6% in Victoria, compared to 1.4% and 2.8% in Denmark with no difference in overall survival ( p = 0.28) or risk‐adjusted survival (HR: 1.10 (95% CI: 0.89–1.37); p = 0.38). Conclusion: High‐quality surgical lung cancer care was confirmed by similar high resection and low mortality rates including no overall survival difference. The drivers and consequences of stage discordance and differences in patterns of resection deserve further exploration. This study provides a model for international benchmarking using clinical quality registries, although caution remains in the interpretation given disparities in data completeness. Abstract : This study provides a model for International benchmarking using clinical quality registries and found similar high resection and low mortality rates including no overall survival difference.